Percutaneous kidney stone surgery and radiation exposure: A review - Bohdan Baralo; Patrick Samson; David Hoenig; Arthur Smith (Asian Journal of Urology)
During the past 3 decades, radiation exposure (RE) has increased drastically among patients undergoing percutaneous nephrolithotomy (PCNL), thus potentially causing new cases of cancer each year. The effective dose received by patients comes from pre- and post-operative computed tomography (CT) and intraoperative fluoroscopy (FL). We reviewed literature to find novel techniques and approaches that help to decrease RE of patients and personnel. We performed PubMed search using keywords percutaneous nephrolithotomy, intraoperative fluoroscopy, radiation exposure, imaging, percutaneous access, ultrasound, computed tomography, endoscopy, reconstruction, innovations, and augmented reality. Forty-four relevant articles were included in this review. As much as 20% of patients with first diagnosed urolithiasis exceed background RE level almost 17-fold. For diagnosing purposes using low-dose and ultra-low-dose CT, as well as low-dose dual energy scan protocols can be efficient ways to decrease RE while maintaining decent accuracy. Patients with urinary stones can be effectively monitored with digital tomosynthesis, ultrasound alone or ultrasound combined with plain film of the abdomen. Percutaneous access (PCA) into the kidney can be performed with reduced or even no RE, using novel PCA methods. REs from conventional imaging techniques during diagnosis and treatment increase probability of non-stochastic radiation effects. Urologists should be aware of protocols that decrease RE from CT and FL in diagnosis and management of urinary stones. Consideration of recently developed imaging modalities and PCA techniques will also aid in adherence to the “as low as reasonably achievable” principle. Keywords: PCNL, Urolithiasis, Reduction of radiation exposure, Percutaneous kidney access, Diagnostic imaging, Training